Restorative Justice Approaches in Criminal Law: Effectiveness and Societal Perceptions in Contemporary Legal Systems - I Made Artana; Tomi Apra santosa; Ahmad Aswar Roa; Andi Bustamin Daeng Kunu; Nurul Miqat (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to analyze the effectiveness of the restorative justice approach in the contemporary criminal law system and examine public perception of its application. Restorative justice is an alternative approach to the retributive criminal law system that emphasizes the restoration of relationships between perpetrators, victims, and society through dialogue, mediation, and shared responsibility. In recent decades, this approach has been widely adopted in various countries in response to the limitations of the conventional criminal system in resolving conflicts in an ongoing manner. The research methods used include qualitative studies through legal policy analysis, case studies, and empirical literature review on restorative justice programs in a number of jurisdictions. The results of the study show that the restorative justice approach has significant effectiveness in reducing recidivism rates, increasing victim satisfaction, and strengthening social cohesion. However, public perceptions of this approach still vary, influenced by factors of legal culture, the level of public trust in law enforcement agencies, and the understanding of the concept of inclusive justice. This study recommends the need for strengthening regulations, training for law enforcement officials, and public education as a prerequisite for the effective integration of restorative justice in the modern criminal justice system